Neural tube defects prevalence does not increase after modification of the folic acid fortification program in Chile. Issue 7 (26th February 2022) - Pardo, Rosa; Vilca, Marcela; Villarroel, Luis; Davalji, Tahera; Obrycki, John F.; Mazumdar, Maitreyi; Avila, Claudia; Mellado, Cecilia
Abstract: Background: In 2000, Chile's Ministry of Health mandated fortification of wheat flour with folic acid at a concentration of 2.2 mg/kg to prevent neural tube defects (NTDs), resulting in a 50% reduction in NTD prevalence. Concerns about possible collateral effects of high folic acid intake led, in 2009, to decrease the folic acid fortification to 1.8 mg/kg of flour. Our study evaluated the impact of this modification on the prevalence of NTDs in Santiago. Methods: This study measured the prevalence of NTDs in live births and stillbirths born in Santiago. We calculated prevalence ratios (PR) and 95% confidence intervals (CI) between pre‐folic acid fortification (1999–2000), post‐folic acid fortification (2001–2009), and post‐modified folic acid fortification (2010–2015) periods for all NTDs and their specific types. We used chi‐square tests to analyze proportions, and a Joinpoint regression to visualize prevalence time trends. Results: The NTD prevalence for the period 2001–2015 was 8.9 per 10, 000 births, which represents a 48% reduction (PR = 0.52; 95% CI = 0.45–0.61; p < .001) from the pre‐folic acid fortification period. During 2010–2015, the NTD prevalence was 9.5/10, 000 births, which was higher, but not statistically significantly different from 2001 to 2009 prevalence of 8.6/10, 000 (PR = 1.11; 95% CI = 0.96–1.30, p = .17). Conclusions: Decreasing the concentration of folic acid fortification was not associated with a statistically significant change in the prevalence of NTDs. Mandatory folic acid fortification continues to be a safe and highly effective policy to prevent NTDs. Future studies should evaluate the prevalence of NTDs across Chile and adherence to folic acid fortification mandates.